The intersection of race, class, and ethnicity in agrarian inequalities, identities, and the social resistance of peasants in Colombia (2015)
The purpose of this study is to add to our understanding of the effects of agrarian transformations on peasants’ identities and economic empowerment in a context of ethnically based expansion of land rights and agribusiness. By focusing on recently granted rural land rights and the expansion of palm oil plantations in Colombia, the effects of the intersection of race, class, and ethnicity on the inequalities, identities, and social resistance of peasants are examined. Other data were derived from qualitative research (interviews) to analyze the specific case of the lower Atrato region of Colombia, where Law 70 provided territorial rights to Afro-descendants. The results found that inequalities, identities, and social resistance are linked to agrarian transformations. The peasants conceptually conflated the social class and racial demands in their struggles before the enactment of multicultural policies; after multiculturalism, social class and race became intertwined with the concept of ethnicity, which facilitated resistance to primitive accumulation. The results suggest that multicultural policies produce challenges related to the identification of beneficiaries of land rights, although the divisive effects are offset by solidarity practices among racial groups. © 2015, © The Author(s) 2015.